The Influence of Service Quality, Price Perception, and Store Atmosphere On Repurchase Intention (Case Study at The Teras Atas Cafe Surabaya) - Pratiwi, Rheza Septiani; Soebandi, Santirianingrum; Dharmani, I. G. A. Aju Nitya (Quantitative Economics and Management Studies, 2020)
Repurchase intention is very influential in developing a business. Many factors affect repurchase intention, including service quality, perception price, and store atmosphere. The purpose of this study was to determine how the influence of service quality, perception price, and store atmosphere both simultaneously and partially effect on repurchase intention. The data was collected using a questionnaire. The research method uses as many random samples of 281 people. The analysis method using SPSS 18. The results of this study indicate that the independent variables simultaneously influence the dependent variable. This research evidenced from the significance value of 0.000 or less than 0.05 and the Fcalculation = 194.777 while the Ftable obtained 2.66 and this meaning that Fcalculation > Ftable. But in partial variable, service quality is not significant into repurchase intention as in the results of testing showing tcalculation = 0.961 < ttable = 1.968 with significance 0.337 > 0.05.